PERAN GLOBAL EDUCATION DALAM PEMBELAJARAN IPS SD - Poerwanti, Jenny Indrastoeti Siti (Jurnal Inovasi Pendidikan, 2009)
This article is intended to describe the meaning and the importance of global education for elementary students, and the implementation of global education in social studies lessons for elementary school. Social Studies in elementary school concerned with people and their interaction with their social and physical environment. This idea suggests the necessity of social study instruction that requires young people to develop attitudes and skill that will allow them to adapt and construct the variety of new knowledge necessary to cope with a future that may be quite different from today's world. Global education recognized interdependence of people living in other places and cultures, and described classroom activities for helping learners increasing their sensitivity to perspectives of people in other places and cultures.